Effects of game-based learning and flipped classroom strategies on performance and reasoning in patient safety education for surgical nursing students - Mohadesehsadat Mehrdad; Sara Jambarsang; Hosseinali Sadeghian; Fatemeh Jabinian; Fatemeh Keshmiri (PLoS ONE, 2025)
Introduction The present study aimed to assess the effect of game-based learning (GBL) on surgical nursing students’ performance and reasoning skills in the management of patient safety incidents in surgical units compared to the flipped classroom method. Method This quasi-experimental study was conducted at Shahid Sadoughi University of Medical Sciences in 2023–2024. One hundred surgical nursing students and surgical nurses participated in this study. In this study, a game-based learning method was implemented in the intervention group, and a flipped classroom method was used in the control group to educate the participants. The student’s reasoning skills in managing patient safety incidents were assessed by a Key Features examination. The participants’ performance was evaluated based on the WHOBARS questionnaire, which includes three sections: Sign-In, Time-Out, and Sign-out. The participants’ reasoning and performance were assessed once before the educational program and twice after the educational interventions (two weeks and two months after the educational program). Data analysis was conducted using descriptive statistics (mean and standard deviation) and Repeated Measures Analysis of Variance in SPSS software version 26. Results The intervention group achieved significantly higher reasoning skill scores than the control group at both Post-test 1 (p < 0.001) and Post-test 2 (p < 0.001). The intervention group showed superior performance compared to the control group at Post-test 1 (p = 0.04). This difference was no longer statistically significant by Post-test 2 (p = 0.63). The effect size of the intervention on reasoning skills was large (partial η² = 0.146), while its effect on performance was moderate (partial η² = 0.03). Conclusion This study demonstrates that game-based learning significantly enhances surgical nurses’ reasoning skills in managing patient safety incidents compared to traditional flipped learning approaches. While the intervention group showed notable short-term performance improvements at the two-week follow-up, these gains diminished over time, suggesting a need for reinforcement strategies to sustain competency.